June 2010 LSAT
Section 5
Question 14

June 2010 LSAT
Section 5
Question 14

Replies

Irina on November 13, 2019

@Ncontrer18,I think the point of these exercises is to use all the premises to reach your conclusion. Both of your examples only use two out of three premises, if we assume that the missing premise is B ->X, the conclusion is reached by applying rules of inference only to premises 1 and 3. We could take transposition of premise 2 but we could not connect it to premises 1 and 3 otherwise:

(1) A-> B

(2) ~X -> ~ D

(3) B -> X

(4) A -> X 1,3

(5) D -> X 2 transposition

(6) A v D ->X 4,5

In your first example, if the missing premise is ~D -> ~A, then we again only use premises 2 and 3 to reach the conclusion:

(1) A -> B

(2) ~X -> ~D

(3) ~D -> ~A

(4) ~X -> ~A 2,3

So the missing premise needs to connect premises 1 and 2 to infer the conclusion:

(1) ~B -> ~A

(2) ~X -> ~ D

(3) ?

(4) ~X -> ~A

We can see that to get from ~X to ~A using all the premises, the logical chain would have to be ~ X -> ~D -> ? -> ~B -> ~A . The missing connection is therefore ~D -> ~B or B -> D .

Let me know if this helps and if you have any other questions.

Nayeli on November 20, 2019

This was very helpful! It made it much simpler, thank you.GET $100

GET $200